Overcoming Obstacles to Progress: Exploring the Causes and Effective Solutions to Employee Resistance to Organizational Change - Alshahrani, Mohammed A.; Basahal, Abdulrahman S. (The Arab Journal of Administration, 2024)
The study aimed to describe employees’ experiences with and expectations of management during organizational change. The paper applied a descriptive qualitative research design with a purposive quota sampling technique. Thirteen Saudi employees from different food and beverage firms were recruited and interviewed using a semi-structured interview protocol. Thematic analysis of English transcripts resulted in the development of three themes that highlight what aspects are important to consider when implementing organizational changes such as value-added taxation programs, from an employee perspective: (a) open communication, (b) training, and (c) timeframe. This research contributes to the literature on the resistance to change in the context of an emerging economy such as Saudi Arabia. Moreover, this paper sheds light on the main causes of and solutions to resistance to organizational change executed by firms and employees. Specifically, it provides practical insights into how open dialogue and training can significantly reduce employee resistance and facilitate smoother transitions during organizational change.